Microneedling with PRP for Acne Scars: A New Tool in Dermatologist Arsenal - A Scoping Review - Meghe Soham R; Madke Bhushan; Singh Adarshlata; Kashikar Yash; Rusia Kaveri (Wolters Kluwer Medknow Publications, 2024)
Acne scars can greatly impact patient quality of life. While treatment options have included mi- croneedling, the recent addition of platelet-rich plasma (PRP) to this regimen has led to an increased popularity of combination treatment. Here, we aimed to review the efficacy of microneedling and PRP therapies and review the literature on combination treatment for acne scars.